Nanoresolution patterning of hydrogenated graphene by electron beam induced C–H dissociation. (9th August 2018) - Liu, Jiangwei; Chen, Song; Papadakis, Raffaello; Li, Hu
Abstract: Direct writing of semi-conductive or insulative nanopatterns on graphene surfaces is one of the major challenges in the application of graphene in flexible and transparent electronic devices. Here, we demonstrate that nanoresolution patterning on hydrogenated graphene can be approached by using electron beam induced C–H dissociation when the electron accelerating voltage is beyond a critical voltage of 3 kV. The resolution of the patterning reaches 18 nm and remains constant as the accelerating voltage is beyond 15 kV. The origin of the nanoresolution pattering as well as the dependence of the resolution on voltage in this technique is well explained by studying the cross-section of the C–H bond under electron impact. This work constitutes a new approach to fabricate graphene-based electronic nanodevices, with the reduced hydrogenated graphene channel utilized as conductive or semi-conductive counterpart in the structure.